2016
DOI: 10.1155/2016/3169751
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antioxidant Capacities and Cytotoxic Effects of Ten Parmeliaceae Lichen Species

Abstract: Parmeliaceae represents the largest and widespread family of lichens and includes species that attract much interest regarding pharmacological activities, due to their production of unique secondary metabolites. The current work aimed to investigate the in vitro antioxidant and cytotoxic activities of the methanol extracts of ten Parmeliaceae species, collected in different continents. Methanol extraction afforded high phenolic content in the extracts. The antioxidant activity displayed by lichens was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 56 publications
0
15
0
2
Order By: Relevance
“…Some studies using extracts from lichen species exhibit antioxidant properties and cell killing effects to non-oral cancer cells [ 14 , 35 ]. However, the authors focused on several antioxidant abilities but only showed an MTT assay for cell killing evidence to cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies using extracts from lichen species exhibit antioxidant properties and cell killing effects to non-oral cancer cells [ 14 , 35 ]. However, the authors focused on several antioxidant abilities but only showed an MTT assay for cell killing evidence to cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Different methods have been used due to the fact that antioxidant compounds can act by distinct mechanisms, each having its specific target within the reaction matrix. Different chemical reactivities may, thus, result in distinct degrees of antioxidant capacity in the various chemical tests (Fernández-Moriano, González-Burgos, Divakar, Crespo, & Gómez-Serranillos, 2016).…”
Section: Effects Of In Vitro Digestion and Colonic Fermentation On Thmentioning
confidence: 99%
“…In order to evaluate the effects of membrane filtration in the antioxidant activity of hibiscus extract, two different methods (DPPH and FRAP) were used due to the fact that antioxidant compounds can act by different radical mechanisms, resulting in different degrees of antioxidant capacity in different trials (Fernández‐Moriano et al., 2016). The membrane filtration process caused some reductions in DPPH and FRAP values, but the extract still maintained its antioxidant property after filtrations.…”
Section: Resultsmentioning
confidence: 99%